(untitled) (Indian Journal of Child Health, 2014)
Acquired demyelinating disorders of central nervous system (CNS) are rare disorders in the pediatric age group and are characterized by demyelination occurring at various sites in the nervous system. Demyelination can involve an isolated CNS site such as brain, spinal cord (transverse myelitis) and optic nerves (optic neuritis) or can involve multiple areas of the nervous system. This group of disorders includes transient single-time events like acute demyelinating encephalomyelitis (ADEM) to life-long conditions like multiple sclerosis (MS). Repeated acute episodes of demyelination may be a harbinger to the development of chronic demyelinating disorders. Early and accurate distinction between transient acute single-time demyelinating events and chronic relapsing conditions like MS is of paramount importance as treatment protocols and prognosis are widely different. Early disease modifying therapy may be beneficial in MS to suppress the ongoing and future relapses, whereas in ADEM, only short-term steroid therapy is all that is needed with an overall good prognosis.